TeSOS-ProteSOS M-health system: a software architecture perspective (2022)
The present thesis document exposes the technical and programmatic component of a system developed jointly by the Central Military Hospital and the Universidad de los Andes using user-centered design methodologies and MHealth technologies supporting (Amputees Unity of amputee patients in rural areas of the country. It presents as results the software architecture decisions, diagrams, design patterns, technologies used, security strategies, among others.